Guidelines for Public Expenditure Management - Potter, Barry H.; Diamond, Jack. (Washington, D.C. : International Monetary Fund, 1999)
This publication is intended for a general fiscal, or general budget, advisor interested in the macroeconomic dimension of public expenditure management
Includes bibliographical references.
osc 13/06/17
Loans
Keywords: Expenditures, Public; Budget; Government spending policy; Finance, Public